Challenges and Solutions in Project-Based Learning to Enhance Speaking Skills with the Expectation Confirmation Model (ECM) - Asef Wildan Munfadlila (Universitas Pendidikan Ganesha, 2026)
Many college students still struggle to develop English-speaking skills due to lecturer-centered teaching practices that offer limited opportunities for authentic oral communication. This condition results in low self-confidence, limited fluency, and minimal engagement in communication activities. This study aims to critically evaluate and model the effectiveness of integrating Project-Based Learning (PjBL) with the Expectation Confirmation Model (ECM). This study used a quantitative, explanatory survey design. A total of 150 students were selected proportionally from a population of 250 using stratified random sampling. Data were collected using a Likert-scale questionnaire. The results showed that all constructs met the criteria for convergent validity, discriminant validity, and reliability. Structurally, expectations significantly influenced confirmation; confirmation significantly influenced perceived usefulness and satisfaction; perceived usefulness increased satisfaction; and satisfaction strongly predicted continuance intention. This study concluded that integrating PjBL and ECM is an effective pedagogical framework for addressing speaking skills while strengthening continued learning engagement. The implications of this research indicate that learning strategies that emphasize students' perceptions of usefulness and satisfaction can improve speaking outcomes and encourage long-term learning commitment.